The age of uncertainty - Galbraith, John Kenneth 1908-2006 (British Broadcasting Corporation, 1977)
The distinguished diplomat and economist surveys the ideas and influence of economists and social philosophers, from Adam Snith's day to the present, contrasting the certainties in ninteenth-century economic thought with the uncertainty of today's.